Revisiting the Spectral Energy Correlations of GRBs with Fermi Data. I. Model-wise Properties - Liang Li (The Astrophysical Journal Supplement Series, 2023)
Gamma-ray bursts (GRBs) exhibit a diversity of spectra. Several spectral models (e.g., Band, cutoff power law (CPL), and blackbody) and their hybrid versions (e.g., Band+blackbody) have been widely used to fit the observed GRB spectra. Here, we attempt to collect all the bursts detected by Fermi/GBM with known redshifts from 2008 July to 2022 May, having been motivated to (i) provide a parameter catalog independent of the official Fermi/GBM team and (ii) achieve a “clean” model-based GRB spectral energy correlation analysis. A nearly complete GRB sample is created, containing 153 such bursts (136 long GRBs and 17 short GRBs). Using the sample and by performing detailed spectral analysis and model comparisons, we investigate two GRB spectral energy correlations: the correlation of the cosmological rest-frame peak energy ( E _p, _z ) of the ν F _ν prompt emission spectrum with (i) the isotropic-bolometric-equivalent emission energy E _γ _,iso (the Amati relation) and (ii) the isotropic-bolometric-equivalent peak luminosity L _p,iso (the Yonetoku relation). From a linear regression analysis, a tight correlation between E _p, _z and E _γ _,iso (and L _γ _,iso ) is found for both Band-like and CPL-like bursts (except for CPL-like long burst E _p, _z – E _γ _,iso correlation). More interestingly, CPL-like bursts do not fall on the Band-like burst Amati and Yonetoku correlations, suggesting distinct radiation processes, and pointing to the fact that these spectral energy correlations are tightly reliant on the model-wise properties.